Heart rate and blood lactate concentration analysis during a high-level men's gymnastics competition - Jemni, M.; Friemel, F.; Lechevalier, J. M.; Origas, M. (The Journal of Strength and Conditioning Research, 2000)
even 18-year-old volunteer French international elite gymnasts participated in a simulation of a competition. Heart rate (HR) was measured by a continuous method, and blood lactate concentration (BL) was measured before and 2, 5, and 10 minutes after each gymnastics event. Mean duration of floor, pommel horse, rings, horizontal bar, and fix bar exercises was 34.70 ± 5.00 seconds, except vaulting, which lasted 5.16 ± 0.40 seconds. High-performance gymnasts required a very high HR (179.49 ± 10.39 b·min1) during a very short time. Each event required a specific HR range. Mean peak BL value was 5.07 mmol·L1 on 5 apparatuses. Vault was significantly less than were those of the other exercises. HR and BL values differed between events. We concluded that the vaulting effort provided a recovery effect on the following events, and we suppose that an active recovery is useful between events.